OPTIMIZING PHARMACEUTICAL DRUG DEVELOPMENT THROUGH WEB-BASED APPLICATIONS: EFFICIENCY, CHALLENGES, AND FUTURE PROSPECTS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The pharmaceutical sector now relies heavily on web-based apps to improve patient care, discover new drugs, and streamline operations. The benefits, drawbacks, and possibilities of web-based applications in pharmaceutics are examined in this paper. A summary of how these applications are changing clinical trials, pharmacovigilance, supply chain management, andpatientinvolvement is provided in the study, which draws on views from pharmaceutical experts. This article emphasizes the real-world uses and potential future paths of these technologies in pharmaceutics by incorporating professional viewpoints.